Gas in India: the transition challenge - Jain, A (Oxford Institute for Energy Studies, 2012)
India is 70 percent import dependent for crude oil, but imported gas (LNG) accounts for just 28 percent of its total gas consumption. With the former comprising 30 percent of India’s primary commercial energy supply against 11 percent of gas (BP Statistical Review of World Energy, 2011), it is evident that unlike oil, imported gas has not featured predominantly in the country’s energy mix. There are several reasons for the limited role to date of natural gas imports on the Indian market – most prominently the difficulty of establishing a transnational gas pipeline and the absence of a long-term pricing policy in Indian gas user industries, which is necessary to support LNG supply contracts. Consequently, and in spite of the proximity of India to large gas deposits in the Gulf, the country is not an important player in the world gas market at present.